Dichotomies, dialectics and dilemmas: New directions for critical leadership studies?. (February 2014) - Collinson, David
This article builds on Fairhurst and Connaughton's proposals for future research agendas in leadership studies by critically examining three key themes in the leadership literature: dichotomies, dialectics, and dilemmas. The first section argues that mainstream leadership research frequently relies on conceptual dichotomies which are often multiple, inter-related, and proliferating. Critiques of dichotomization are suggestive of more dialectical forms of analysis and these are discussed in the second section. Dialectical studies can surface important questions about organizational power relations, paradoxes and contradictions that are typically under-explored within mainstream leadership studies. The third section proposes an additional, future research theme for critical perspectives, namely whether and if so why, how, and with what consequences leaders may engage in discourses of denial regarding the dilemmas and tensions of organizational life. The article concludes by arguing that re-framing leadership dichotomies as multiple, intersecting dialectics can open up fresh lines of enquiry and generate important insights about the complex and situated relations of power and identity that comprise leadership and followership dynamics.